The One Giant Leap commercial wireless power meter can be used for sprint kayaking with the appropriate calibration - Goreham, Joshua A.; Ladouceur, Michel (Frontiers in Physiology, 2025)
PurposeTwo experiments were conducted to determine the construct and concurrent validity of a commercial kayak paddle shaft power meter (OGL) for measuring force and power output in female sprint kayakers.Methods and ResultsConstruct validity: Seven female participants used the same OGL paddle to complete 30 s trials at different stroke rates (60, 80, 100, maximum strokes per minute) while a global positioning system measured kayak velocity. Regression analysis provided a large coefficient of determination (R2≥0.83) between mean power and mean velocity (f(x) = 6.892 × 3). Concurrent validity: Two known weight combinations were used to calibrate the paddle (wide range: 51.5–394.9 N; narrow range: 100.6–247.7 N), whereas both left and right sides of the shaft were statically loaded eight separate times with known weights (51.5 N–394.9 N at 49.1 N intervals) to test its concurrent validity. The right side of the shaft had proportional bias (p < 0.001) and the left side of the shaft had fixed bias (65.7 ± 21.1 N, p = 0.017) when calibrated with a narrow range. Neither shaft side had proportional bias, but both shaft sides had small, fixed biases (left: 18.3 ± 7.4 N, p = 0.043; right: 9.3 ± 3.0 N, p = 0.018) when calibrated with a wide range.ConclusionThe study establishes that even though the OGL reports power values that appear to have construct validity up to 4.6 m s-1, calibration with a range of weights that encompasses the projected applied forces is needed to improve the accuracy of the force measurement, and thus the power calculation, by the OGL.